Investigating the concept of Egyptian dwelling - Hulin, L; Rocha da Silva, T (Institute Français d'Archéologie Orientale/Polish Centre of Mediterranean Archaeology University of Warsaw, 2023)
This paper explores the concept of dwelling within the Egyptian world in the New Kingdom. Rather than focussing upon the house and household as an economic unit or as an indication of relations between the individual and the state, it is the social concept of dwelling, the habitus, that is the focus of this paper, especially the relationship between social practices and habits and the extent to which this is modified and adapted to new environments and different social landscapes. The underlying argument is that dwelling is distributed across the lived environment, with domestic activities never solely confined to the four walls of a house or its compound. Currently, we rely upon typologies of houses and domestic life that assume a standardised definition of Egyptian life regardless of the environment, but this is by no means proven. A specifically Egyptian mode of dwelling has been most discussed in the empire, where the self-definition of the rulers and the ruled in part of the functioning of the imperial mechanism. We also argue for the need to establish whether lifeways in the Nile Valley were the same as lifeways in the Delta.